2004
DOI: 10.1152/ajprenal.00213.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tyrosine kinase blockade on norepinephrine-induced cytosolic calcium response in rat afferent arterioles

Abstract: We used genistein (Gen) and tyrphostin 23 (Tyr-23) to evaluate the importance of tyrosine phosphorylation in norepinephrine (NE)-induced changes in intracellular free calcium concentration ([Ca(2+)](i)) in rat afferent arterioles. [Ca(2+)](i) was measured in microdissected arterioles using ratiometric photometry of fura 2 fluorescence. The control [Ca(2+)](i) response to NE (1 microM) consisted of a rapid initial peak followed by a plateau phase sustained above baseline. Pretreatment with the tyrosine kinase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…PTK and/or PTP mediated BK Ca a subunit tyrosine phosphorylation and BK Ca activation could lead to the hyperpolarization of VSMC membrane and the close of voltage-sensitive calcium channel, which could facilitate the development of vascular hyporesponsiveness in hemorrhagic shock. Salomonsson and Arendshorst reported that genistein could inhibit the NE-induced vasoconstriction through decreasing intracellular [Ca 2+ ] and the sensitivity of contractile apparatus to Ca 2+ at higher concentration (5 Â 10 À 2 mol/L) [22], while genistein induced the restitution of the decreased vascular reactivity in the present study at much lower concentration (10 À 5 mol/L). It was suggested that genistein could have different dose-dependent effects on NE-induced vasoconstriction and vascular reactivity through different mechanisms.…”
Section: Discussionsupporting
confidence: 44%
“…PTK and/or PTP mediated BK Ca a subunit tyrosine phosphorylation and BK Ca activation could lead to the hyperpolarization of VSMC membrane and the close of voltage-sensitive calcium channel, which could facilitate the development of vascular hyporesponsiveness in hemorrhagic shock. Salomonsson and Arendshorst reported that genistein could inhibit the NE-induced vasoconstriction through decreasing intracellular [Ca 2+ ] and the sensitivity of contractile apparatus to Ca 2+ at higher concentration (5 Â 10 À 2 mol/L) [22], while genistein induced the restitution of the decreased vascular reactivity in the present study at much lower concentration (10 À 5 mol/L). It was suggested that genistein could have different dose-dependent effects on NE-induced vasoconstriction and vascular reactivity through different mechanisms.…”
Section: Discussionsupporting
confidence: 44%
“…Afferent arteriolar calcium entry and release associated with afferent arteriolar constriction with angiotensin II [Che and Carmines, 2002] and norepinephrine [Salomonsson and Arendshorst, 2004] were also reduced by TyrK blockade. The L-type calcium channel blocker, nifendipine had no effect on calcium entry in the TyrK-blockertreated arterioles suggesting that TyrK plays a major role in calcium entry during norepinephrine contraction [Salomonsson and Arendshorst, 2004]. It is clear that there is an interaction between vasoconstrictor agonists and TyrK activity, particularly the TyrK of the EGF receptor.…”
Section: Tyrosine Kinases Modulate G Protein Coupled Receptorsmentioning
confidence: 90%
“…When a TyrK inhibitor (AG1478) that specifically blocks the epidermal growth factor receptor (EGFR) TyrK was administered, the constriction to Angiotensin II in afferent and efferent arterioles was reduced 52% and 51%, respectively, suggesting that renal afferent arteriolar constriction to angiotensin II is most affected by the EGFR form of TyrK. Afferent arteriolar calcium entry and release associated with afferent arteriolar constriction with angiotensin II [Che and Carmines, 2002] and norepinephrine [Salomonsson and Arendshorst, 2004] were also reduced by TyrK blockade. The L-type calcium channel blocker, nifendipine had no effect on calcium entry in the TyrK-blockertreated arterioles suggesting that TyrK plays a major role in calcium entry during norepinephrine contraction [Salomonsson and Arendshorst, 2004].…”
Section: Tyrosine Kinases Modulate G Protein Coupled Receptorsmentioning
confidence: 99%
“…Several studies have shown that under normal circumstances, genistein can inhibit the contraction of kidney blood vessels, including glomerular arterioles, afferent arteries, or vascular beds [140][141][142]. In addition, genistein can inhibit norepinephrine-induced vasoconstriction, but this effect is not completely dependent on extracellular Ca 2+ [143].…”
Section: The Effects Of Genistein On Kidney Ischemia/reperfusion Injurymentioning
confidence: 99%